Open deuren : kunst in woonbiotoop met de buurtbewoner als curator. - Croxhapox, Gent (Gent : Croxhapox Gent, 1996)
Vercaemer, Koen ; Borremans, Michaël ; de Timmerman, Mario ; Jacobs, Carl ; Baele, Patrick ; Vandamme, Koen ; Debrabanter, Walter ; Bauters, Tini ; Devens, Zjuul ; van Camp, Els ; Depuydt, Piet ; Minne, Luc ; Van Roy, Johan ; Clicque, Robert ; Vandenberg, Philippe ; Vlerick, Erwin ; Clément, Daniëlle ; de Clercq-Vandenberghe, ; Vasic, Zoriça ; Popova, Roumiana ; Dewindt, Peter ; Cox, Wouter ; Serie, Sarah ; Suykens, Geert ; Jacquet, Alexandra ; Suykens, Guido ; Herbie ; L'escamoteur ; Suykens, Carien ; Suykens, Hilde ; de Neef, Dirk ; Demasure, Krist ; Mistiaen, Thomas ; Broadbent, Thomas ; Devos, Ignace ; van Vlierberghe, Marc ; Dept, Veronique ; Pannecoucke, Odette ; Jacobs, Rieke ; Schrauwen, Wim ; Slangen, Bart ; Slock, Lucy ; Braeckman, Dirk ; Paridaen, Sjoerd ; Vanderhaegen, Koen ; Deceuninck, Damien ; Simoen, Peter ; Capovilla, Giampaolo ; Baele, Guy ; De Clercq, Marc ; Coddens, Eddy ; Lauwaert, Beatrijs ; Cappelle, Claire ; Albrecht, Anne ; Siemerink, Mieke ; van Maanen, Ron ; Deruyck, Tine ; de Prez, Peter ; Vermeulen, Philippe ; Kizumi ; De Smet, Teresa ; Decraemer, Chris ; Huvenne, Martine ; Fryns, Martin ; d'Hondt, Mieja ; Duportaille, Walter ; Marion ; Perguy-Naessens, Katrien & Marc ; Casaer, Randall ; Februtte, Louis ; De Leener, Hugo ; Hoflack, Marc ; Lanoye, Caroline ; Coessens, Veerle ; D'Hondt, Lieve ; Ghyselen, Yves ; Bultinck, Jo ; van Dijck, Siene ; Ginger & Fred ; Cosijns, Sylvain ; de Roder, Vincent ; Lein, Peter
Nederlands
Open deuren : kunst in woonbiotoop met de buurtbewoner als curator, Croxhapox Gent, 28.09.1996 - 06.10.1996
boek